Greater Trochanteric Pain Syndrome: Epidemiology and Associated Factors - Segal, Neil A.; Felson, David T.; Torner, James C.; Zhu, Yanyan; Curtis, Jeffrey R.; Niu, Jingbo; Nevitt, Michael C. (Archives of physical medicine and rehabilitation, 2007)
Segal NA, Felson DT, Torner JC, Zhu Y, Curtis JR, Niu J, Nevitt MC, for the Multicenter Osteoarthritis (MOST) Study Group. Greater trochanteric pain syndrome: epidemiology and associated features. To describe the prevalence of greater trochanteric pain syndrome (GTPS); to determine whether GTPS is associated with iliotibial band (ITB) tenderness, knee osteoarthritis (OA), body mass index (BMI), or low back pain (LBP); and to assess whether GTPS is associated with reduced hip internal rotation, physical activity, and mobility. Cross-sectional, population-based study. Multicenter observational study. Community-dwelling adults (N=3026) ages 50 to 79 years. Not applicable. Greater trochanteric tenderness to palpation in subjects with complaints of hip pain and no signs of hip OA or generalized myofascial tenderness. The prevalence of unilateral and bilateral GTPS was 15.0% and 8.5% in women and 6.6% and 1.9% men. Odds ratio (OR) for women was 3.37 (95% confidence interval [CI], 2.67−4.25), but age and race were not significantly associated with GTPS. In a multivariate model, adjusting for age, sex, ITB tenderness, ipsilateral and contralateral knee OA, BMI, and LBP, ITB tenderness (OR=1.72; 95% CI, 1.34−2.19), knee OA ipsilaterally (OR=3.47; 95% CI, 2.72−4.42) and contralaterally (OR=1.74; 95% CI, 1.32−2.28), and LBP (OR=2.79; 95% CI, 2.22−3.50) were positively related to GTPS. In this complete model, BMI was not associated with GTPS (OR=1.10; 95% CI, 0.80−1.52 when comparing ≥ 30 with <25kg/m 2). Hip internal rotation range of motion did not differ based on GTPS status. After multivariate adjustment, GTPS did not alter physical activity score, but bilateal GTPS was significantly associated with a higher 20-meter walk time and chair stand time. The higher prevalence of GTPS in women and in adults with ITB pain or knee OA indicates that altered lower-limb biomechanics may be related to GTPS. Slower functional performance in those with GTPS suggests that the study of targeted rehabilitation may be useful. A longitudinal study will be necessary to identify causal factors and outcomes of interventions.